1998
DOI: 10.3354/meps172253
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface dinoflagellate populations, frontal blooms and the formation of red tide in the southern Benguela upwelling system

Abstract: ABSTRACT-The West Coast of South Africa is often subjected to problems associated with red tides which are usually attributed to blooms of migratory dinoflagellates. This study investigates the coupling between the physical environment and the biological behaviour and physiological adaptation of dinoflagellates in an attempt to understand bloom development, maintenance and decline. Widespread and persistent subsurface dinoflagellate populations domlnate the stratified waters of the southern Benguela during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 9 publications
2
71
0
1
Order By: Relevance
“…These localized autumn events appeared as visible and spatially delimited patches of red water. Red-water blooms of similarly high concentrations observed in this study (up to 70 µg l -1 ) have also been described to occur most frequently during autumn in the Southern Benguela (Horstman 1981, Pitcher & Boyd 1996, Pitcher et al 1998, Mitchell-Innes et al 2000. Because dinoflagellates grow well at low irradiances (Richardson et al 1983) and are highly motile (e.g.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These localized autumn events appeared as visible and spatially delimited patches of red water. Red-water blooms of similarly high concentrations observed in this study (up to 70 µg l -1 ) have also been described to occur most frequently during autumn in the Southern Benguela (Horstman 1981, Pitcher & Boyd 1996, Pitcher et al 1998, Mitchell-Innes et al 2000. Because dinoflagellates grow well at low irradiances (Richardson et al 1983) and are highly motile (e.g.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, relaxation of upwelling winds often causes landward advection of plankton in the California Current System (Small & Menzies 1981, Roughgarden et al 1991, Shanks 1995. Moreover, Pitcher et al (1998) observed dinoflagellate-dominated, frontal blooms during the onshore movement of warmer, maturing-upwelled water following upwelling (i.e. during relaxation).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Se han señalado las interacciones como la combinación de vientos, surgencias, frentes de densidad, concentraciones de nutrientes o alteraciones antropogénicas (Alonso & Ochoa 2004, Buschmann 2005, Pitcher et al 1998, Ryan et al 2009, Kudela et al 2005. La intensidad y distribución geográfica de las floraciones algales causadas por dinoflagelados y diatomeas han aumentado en las últimas décadas, asociadas a cambios climáticos locales o globales (Wells et al 2015, Klais et al 2011, Hinder et al 2012, Edwards et al 2006, Reguera 2002, Hallegraeff 1993; así como también el incremento de los reportes de casos de intoxicación humana y graves pérdidas económicas en la industria pesquera (Brooks et al 2016, Sanseverino et al 2016, Berdalet et al 2015, Ferrante et al 2013, Anderson et al 2002, Anderson et al 2000.…”
Section: Introductionunclassified
“…The need to mitigate the deleterious effects of HABs has prompted a large amount of research in several coastal areas (e.g. Figueiras et al 1994, Tester & Steidinger 1997, Pitcher et al 1998, Anderson et al 2005a, from which we have learned much about the dynamics of these blooms. Still, the initiation phase remains one of the least understood aspects of HAB dynamics.…”
Section: Introductionmentioning
confidence: 99%